Absence of circulating mast cell precursors in paediatric mastocytosis: could it reflect a different pathophysiology between adults and children with mastocytosis?. (14th June 2013) - Georgin‐Lavialle, S.; Le Saché‐de Peufeilhoux, L.; Martin, L.; Soucie, E.; Bruneau, J.; Barete, S.; Dubreuil, P.; Bodemer, C.; Hermine, O.; Lhermitte, L.
Abstract Background Mastocytosis is a heterogeneous disease whose different subtypes also vary in aggressivity. Children typically present with cutaneous mastocytosis. We identified, in our previous work, a peripheral CD34‐c‐Kit+mast cell precursor by flow cytometry in systemic forms but not in cutaneous forms of adult mastocytosis. Objectives We wanted to know if such a mast cell precursor exists among children with mastocytosis. Methods We analysed 10 children with mastocytosis for c‐Kit+CD34‐ mast cell precursors by flow cytometry. Results In contrast to adults with mastocytosis, we did not detect any circulating mast cell precursors by flow cytometry in the peripheral blood of children with mastocytosis. Conclusion The clinical symptoms observed among children with cutaneous mastocytosis could be induced by cutaneous mast cell mediators and not by circulating mast cells. These results may help to better understand the differences between adult and childhood mastocytosis.